Taking the Long View: Cultivating Historical Thinking in Elementary Teacher Education. Issue 1 (2nd January 2018) - Currin, Elizabeth; Schroeder, Stephanie
ABSTRACT: As new teachers confront the realities of a Trump administration characterized by a troublingly tenuous grasp of history, we advocate for infusing historical thinking into all facets of elementary teacher education. Historical thinking can promote an inquiry stance, ably contribute to social justice initiatives, and enable teachers to appreciate their place within a long and storied tradition. Acknowledging challenges to such thinking—particularly in the Trump era—we offer proactive recommendations, maintaining that historical thinking goes beyond the purview of history and social studies and should be infused throughout teacher education and cultivated as a stance in elementary teacher candidates.